PENGARUH KEADILAN ORGANISASIONAL TERHADAP KINERJA MANAJERIAL PERUSAHAAN BUMN DI MALUKU DENGAN KEPERCAYAAN PADA ATASAN SEBAGAI VARIABEL MEDIASI - Salomi J. Hehanussa (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
This study aims to examine procedural justice, distributive justice, and interactive justice perceived by manager in the workplace about the treatment received from organization on their outcomes by using theory of planned behavior, organizational justice theory, and expectancy theory. The outcomes shown by managers include trust in supervisor and managerial performance. This study uses survey method in collecting data and sample selection method at state-owned companies in Maluku Province represented by 310 middle and lower managers. The hypotheses are tested by Structural Equation Modeling.    The results show that procedural justice and interactive justice has significant influence on managerial performance, whereas distributive justice has no influence on managerial performance. Empirical evidences show that distributive justice and interactive justice has influence on trust in supervisor, whereas procedural justice has no influence on trust in supervisor. Trust in supervisor also has influence on managerial performance. Keywords: Procedural Justice, Distributive Justice, Interaction Justice, Trust in Supervisor, Managerial Performance.